SYSTRUST ANALYSIS OF THE ELECTRONIC TAX APPLICATIONS BASED-ON TECHNOLOGY ACCEPTENED MODEL - Karima Suci Ariani; Endang Kiswara (Diponegoro Journal of Accounting, 2021)
This study aims to determine and analyze systrust of 8 electronic tax applications to the indicators of security, availability, processing integrity, confidentiality, and privacy based on dimensions of ease of use, usefulness, attitudes, and behavioral intentions. This research also aims to find out which electronic tax applications has the best systrust. Research population is 15 electronic tax applications provided by the Directorate General of Taxes (DGT). While, research sample is 8 electronic tax applications. This research collaborates primary data form applications observasion, study documentation, and experimental results from dummy data.This research shows systrust of the e-faktur application is118, e-SPT of income tax article 21/26 is119, e-SPT of corporate income tax is 121, e-SPT of personal income is114, e-SPT of income tax article 4 (2) is 116, e -SPT of income tax article 23-26 is117, e-SPT of income tax article 22 is 121, and e-SPT of income tax article 15 is 121. Based on research results it is also known that e-SPT of corporate income tax, e-SPT of income tax article 22, and e-SPT of income tax article 15 are applications with the highest systrust. Meanwhile, e-SPT of personal income is application with the lowest systrust.